Cytoprotective Effect of Morinda tinctoria Roxb. against Surgical and Chemical Factor Induced Gastric and Duodenal Ulcers in Rats. (25th December 2011) - Sivaraman, D.; Muralidharan, P.
Abstract : The present paper relates to the pharmacological validation of the antiulcer efficacy of ethanol leaf extract of Morinda tinctoria Roxb. (EEMT) against aspirin pyloric ligation-induced gastric ulcer model and cysteamine-induced duodenal ulcer in Wistar rats. Oral administration of EEMT at a dose of 200 and 400 mg/kg significantly prevented the occurrence of aspirin pyloric ligation and cysteamine-induced gastric and duodenal ulceration. The volume and acidity of gastric juice in pyloric ligated rats were significantly (P < 0.01 ) reduced by EEMT. There was a significant decrease in the number of ulcers, and its severity in both the models proved the ulcer protective activity of EEMT. Administration of extract at both dose levels has shown a significant increase in potassium and sodium ion concentration in the gastric juice of pylorus ligation group. On the basis of these observations, we concluded that EEMT possessing antiulcer activity may be due to the modulation of defensive factors by improvement in gastric cytoprotection.